2020
DOI: 10.1016/j.redox.2019.101356
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide attenuates cigarette smoke-induced airway remodeling by upregulating SIRT1 signaling pathway

Abstract: Airway remodeling is one of the characteristics for chronic obstructive pulmonary disease (COPD). The mechanism underlying airway remodeling is associated with epithelial-mesenchymal transition (EMT) in the small airways of smokers and patients with COPD. Sirtuin 1 (SIRT1) is able to reduce oxidative stress, and to modulate EMT. Here, we investigated the effects and mechanisms of hydrogen sulfide (H2S) on pulmonary EMT in vitro and in vivo. We found that H2S donor NaHS inhibited cigarette smoke (CS)-induced ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 50 publications
2
54
0
Order By: Relevance
“…We did find airway remodelling in COPD patients and CS‐exposed mice, manifesting as collagen deposition and epithelial‐mesenchymal transition (EMT). These findings are in accordance with previous observations 32,33 . During this process, myofibroblasts, which originate directly from lung bronchial fibroblasts, are involved in the formation of airway fibrosis 34 .…”
Section: Discussionsupporting
confidence: 93%
“…We did find airway remodelling in COPD patients and CS‐exposed mice, manifesting as collagen deposition and epithelial‐mesenchymal transition (EMT). These findings are in accordance with previous observations 32,33 . During this process, myofibroblasts, which originate directly from lung bronchial fibroblasts, are involved in the formation of airway fibrosis 34 .…”
Section: Discussionsupporting
confidence: 93%
“…It was also revealed that H 2 S inhibited airway remodeling caused by CS by attenuating oxidative injury and epithelial-mesenchymal transition. 53 Perry et al . 54 reported that H 2 S inhibited the proliferation of smooth muscle and cytokine release in airway.…”
Section: Discussionmentioning
confidence: 99%
“…All experimental protocols were approved by the Ethics Committee of Animal Experiments of Guangzhou Medical University. Mice were exposed to cigarette smoke (CS) as described previously [ 27 ]. The control mice were exposed to clean air.…”
Section: Methodsmentioning
confidence: 99%